Bioremediation approaches in a laboratory activity for the Industrial Biotechnology and Applied Microbiology (IBAM) course - Raiger Iustman, Laura Judith (2013)
Industrial Biotechnology and Applied Microbiology is an optional 128h-course for Chemistry and Biology students at the Faculty of Sciences, University of Buenos Aires, Argentina. This course is usually attended by 25 students, working in teams of two. The curriculum, with 8 lab exercises, includes an oil bioremediation practice covering an insight of bioremediation processes: the influence of pollutants on autochthonous microbiota, biodegrader isolation and biosurfactant production for bioavailability understanding. The experimental steps are: (A) evaluation of microbial tolerance to pollutants by constructing pristine soil microcosms contaminated with diesel or xylene and (B) isolation of degraders and biosurfactant production analysis. To check microbial tolerance, microcosms are incubated during one week at 25-28ºC. Samples are collected at 0, 4 and every 48 h for CFU/g soil testing. An initial decrease of total CFU/g related to toxicity is noticed. At the end of the experiment, a recovery of the CFU number is observed, evidencing enrichment in biodegraders. Some colonies from the CFU counting plates are streaked in M9-agar with diesel as sole carbon source. After a week, isolates are inoculated on M9-Broth supplemented with diesel to induce biosurfactant production. Surface tension and Emulsification Index are measured in culture supernatants to visualize tensioactive effect of bacterial products. Besides the improvement in the good microbiological practices, the students show enthusiasm in different aspects, depending on their own interests. While biology students explore and learn new concepts on solubility, emulsions and bioavailability, chemistry students show curiosity in bacterial behavior and manipulation of microorganisms for environmental benefits.